2016
DOI: 10.1521/pdps.2016.44.1.39
|View full text |Cite
|
Sign up to set email alerts
|

Varieties of Castration Experience: Relevance to Contemporary Psychoanalysis and Psychodynamic Psychotherapy

Abstract: Although Freud considered castration to be one of the two major anxieties of human life, the castration complex has been relatively neglected in contemporary psychoanalytic writing and is insufficiently discussed in presentations of clinical cases. This article discusses the relevance of the concept to contemporary psychoanalysis and psychodynamic psychotherapy, in particular the important contributing role of castration conflicts in the pathogenesis of a wide range of clinical symptoms. The author begins by b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
2
2

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…When my patient first entered treatment, his drawings and perversion seemed to represent failed efforts to repair the self and free himself from a persecutory internal bad object. The removal of his beard, and the analogy he later made to a wolf amputating its leg to escape from a hunter's trap, suggested that his impotence and inhibited creativity were symbolic selfcastrations (Taylor 2016). Indeed, Eric said that without the perversion he would feel as if he did not have a penis.…”
Section: Discussionmentioning
confidence: 99%
“…When my patient first entered treatment, his drawings and perversion seemed to represent failed efforts to repair the self and free himself from a persecutory internal bad object. The removal of his beard, and the analogy he later made to a wolf amputating its leg to escape from a hunter's trap, suggested that his impotence and inhibited creativity were symbolic selfcastrations (Taylor 2016). Indeed, Eric said that without the perversion he would feel as if he did not have a penis.…”
Section: Discussionmentioning
confidence: 99%
“…Over the past two decades, psychoanalysts have come to use the term castration not only literally but also symbolically and as a metaphor for injury to or loss of some valued part of the self. There is recognition also that the penis often serves as a metaphor for power, thus rendering some men vulnerable to narcissistic mortification and feelings of humiliation and shame as they question and compare their achievements and sexual performance in relation to other men (Taylor 2016).…”
Section: Introductionmentioning
confidence: 99%